Manajemen Tata Kelola Kota Medan Melalui Pendekatan Reduce at Source dan Resource Recycle - Heru Syahputra (UIN Sumatera Utara, 2021)
Abstract. Garbage is an important problem faced by several cities in Indonesia. These problems are more concentrated on waste management. The limited area of land for landfills affects waste management, especially waste disposal services. Only waste can be transported and disposed of to the TPA, while the rest is scattered in various places. The presence of garbage in Medan City is one of the problems faced by the community and city managers. especially in terms of providing facilities and infrastructure. The amount of this waste is expected to continue to increase, where the growth rate is every year. Piles of garbage that disturb the health and beauty of the environment are a type of pollution that can be classified as social environmental degradation. Based on the Regulation of the Minister of Environment Number 13 of 2012 concerning Guidelines for the Implementation of Reduce, Reuse and Recycle, government officials and the community can work together in implementing waste management to create a clean and healthy environment. So far, the implementation of waste management has only relied on the collect, transport, and disposal approach by relying on the existence of a final processing site (TPA). In this journal, the problem formulated is how to implement waste management in the city of Medan by using the reduce at source and resource recycle approach through the implementation of 3R (Reduce, Reuse and Recycle)? The research method used in this journal is a qualitative descriptive research method. Therefore, all levels of society and the government of the city of Medan are expected to change their paradigm towards waste, namely seeing waste as something that has use value and benefits, so that it can treat waste as an alternative resource can be reused, either directly, the recycling process, or other processes.Keywords: Waste Management; Urban.